Unexpected equivalent potency of a constrained chromene enantiomeric pair rationalized by co-crystal structures in complex with estrogen receptor alpha. Issue 7 (1st April 2019) - Zhang, Birong; Kiefer, James R.; Blake, Robert A.; Chang, Jae H.; Hartman, Steven; Ingalla, Ellen Rei; Kleinheinz, Tracy; Mody, Vidhi; Nannini, Michelle; Ortwine, Daniel F.; Ran, Yingqing; Sambrone, Amy; et al.
Graphic abstract: Abstract: Despite tremendous progress made in the understanding of the ERα signaling pathway and the approval of many therapeutic agents, ER+ breast cancer continues to be a leading cause of cancer death in women. We set out to discover compounds with a dual mechanism of action in which they not only compete with estradiol for binding with ERα, but also can induce the degradation of the ERα protein itself. We were attracted to the constrained chromenes containing a tetracyclic benzopyranobenzoxepine scaffold, which were reported as potent selective estrogen receptor modulators (SERMs). Incorporation of a fluoromethyl azetidine side chain yielded highly potent and efficacious selective estrogen receptor degraders (SERDs), such as16aa and surprisingly, also its enantiomeric pair16ab . Co-crystal structures of the enantiomeric pair16aa and16ab in complex with ERα revealed default (mimics the A-D rings of endogenous ligand estradiol) and core-flipped binding modes, rationalizing the equivalent potency observed for these enantiomers in the ERα degradation and MCF-7 anti-proliferation assays.